Association of Malnutrition with Delayed Speech among Children 2-6 Years Undergoing Speech Therapy at Rehabilitation Center - Ali, Muzafar; Khan, Erum; Khan, Muhammad Nasir; Khan, Ameer Ullah (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To determine the association of malnutrition with delayed speech children who underwent speech therapy. METHODOLOGY: A descriptive cross-sectional study was conducted enrolling 138 children age 2 to 6 years, with delayed speech, and of both gender, using non-probability consecutive sampling technique at the speech therapy department of National Institute of Rehabilitation Medicine, Islamabad from October 2019 - March 2020. Children with all congenital abnormalities which can impaired speech, deaf, age more than 06 or below 2 years, and cases whose parents do not provide consent to participate in the study were excluded. Data was collected after seeking consent from the guardian of the respondent through a pre-developed scale to assess nutrition status and delayed speech was assessed by underachievement of verbal, reading, and spelling. The data were analyzed through SPSS 23.0. RESULTS: Most of the respondents were male (72.5%), residents of urban areas (84.1%), and not going to schools (60.9%). 79% were rich and well-nourished (68.1%), in speech level-I (59.4%). No relationship was observed between malnutrition and delayed speech level (p-value=0.30). Age, education status, residential status, and monthly income were found in association with delayed speech (p-value <0.00). CONCLUSION: There was no significant relationship between malnutrition and delayed speech level. KEYWORDS: Nutrition, Malnutrition, speech, delay speech, children, speech therapy.